Exploring the distribution and fate of bisphenol A in an aquatic microcosm combined with a multimedia model - Dan Liu; Guodong Kang; Yixi Zhang; Lili Shi; Bo Ma; Shenghu Zhang; Guojian Lu (Ecotoxicology and Environmental Safety)
Bisphenol A (BPA), a well-known endocrine-disrupting chemical, has garnered significant attention in environmental science and policy. BPA can enter the aquatic environment through different routes, posing potential risks even at a low concentration. In this study, a four-compartment system [water, sediment, biota (zebrafish), and submerged aquatic vegetation (Vallisneria natans)] of a point source continuous discharge microcosm was established to investigate the distribution and fate of BPA in an aquatic microcosm. The fugacity model generated predicted values were highly consistent with those of the experiments. The distribution of BPA in the model indicates that sediment was the dominant sink. The residence time of reaction and advection was 5.8 and 75.2 d, respectively, which showed that BPA was mainly removed from the aquatic microcosm through the reaction in biota (58 %). Sensitivity analysis revealed that emission data were the most influential parameters for the model output. Transfer processes between the water and biota phases had a closer relationship. This study provides technical support for pollution source management and risk assessment for BPA.